2017
DOI: 10.1016/j.exger.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric changes in the aging rat brain and its impact on cognitive and locomotor functions

Abstract: Impairments in cognitive and locomotor functions usually occur with advanced age, as do changes in brain volume. This study was conducted to assess changes in brain volume, cognitive and locomotor functions, and oxidative stress levels in middle- to late-aged rats. Forty-four male Sprague-Dawley rats were divided into four groups: 14, 18, 23, and 27months of age. H magnetic resonance imaging (MRI) was performed using a 7.0-Tesla MR scanner system. The volumes of the lateral ventricles, medial prefrontal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
39
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 47 publications
14
39
4
Order By: Relevance
“…At the age of 48 weeks a two-fold increase in MDA concentrations was found as compared with both the ages of 12 and 24 weeks. The results of this study showing increased MDA concentrations with aging are apparently similar to the results of the study by Hamezah et al, (19) which showed increased MDA concentrations and decreased glutathione peroxidase (GPx) concentrations in older rats (27 weeks). The linear increase in MDA concentration started in 18-to 27-week old rats.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…At the age of 48 weeks a two-fold increase in MDA concentrations was found as compared with both the ages of 12 and 24 weeks. The results of this study showing increased MDA concentrations with aging are apparently similar to the results of the study by Hamezah et al, (19) which showed increased MDA concentrations and decreased glutathione peroxidase (GPx) concentrations in older rats (27 weeks). The linear increase in MDA concentration started in 18-to 27-week old rats.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to the increase in brain ventricular volume, the volume of the cerebellum apparently also increases with age. (19) Apparently both of these caused the increases in brain weight in this study.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…During normal aging, it is well established that there is a reduction in the surface area and cortical thickness, resulting in a volume loss in the whole brain, being the non-cortical regions, such as the hippocampus and striatum, more vulnerable to this age-related atrophy [111]. In this context, a study performed with Sprague-Dawley rats of 14, 18, 23, and 27 months of age showed changes in the volume of different brain parts using magnetic resonance imaging (MRI) [112]. In that study they showed enlargement of lateral ventricles and a decrease in the volume of the medial prefrontal cortex, hippocampus, and striatum in 27-month-old rats, which correlates with cognitive deficiency.…”
Section: Mitochondrial Dysfunction and Cognitive Impairmentmentioning
confidence: 99%